Analisis kontrol lingkungan dalam kegiatan preservasi preventif di Perpustakaan Kandaga Universitas Padjadjaran pasca pandemi - Graceline Esterini Mulyana; Saleha Rodiah (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
After being passive for approximately two years due to the pandemic, the library must carry out many recovery activities to restore environmental conditions to improve. During this time the library room is almost always closed, so it is very likely to be damp and dusty. To save it, the library can do something called environmental control. Environmental control is included in preventive preservation activities. This study aims to analyze environmental control in preventive preservation activities at the Kandaga Library, Padjadjaran University after the pandemic. The method used in this study is a qualitative descriptive method with a case study approach. Data was collected using in-depth interviews, observation, and literature studies. The results of this study indicate that environmental control activities in preventive preservation at the Kandaga Unpad Library after the pandemic have changed slightly from the period before the pandemic, where this difference lies in the intensity of its application. The Kandaga Library of Padjadjaran University carries out post-pandemic environmental control of three collection damage factors, namely physical factors which include light, temperature and humidity, and air pollution; chemical factors that are interrelated between the internal conditions of the collection and physical factors; and biological factors, namely insects, fungi, and rodents. However, of the three, for now the library prioritizes physics. This is done because considering these factors have the most significant impact on changes in the physical condition of the collection. The implementation of activity control in the Kandaga Library is still carried out using a simple method.